Genetic Conservation and Medicinal Properties of Mate (Ilex paraguariensis St Hil.) - Cansian, R.L.; Mossi, A.J.; Mosele, S.H.; Toniazzo, G.; Treichel, H.; Paroul, N.; Oliveira, J.V.; Oliveira, D.; Mazutti, M.; Echeverrigaray, S. (Pharmacognosy Reviews)
This work provides an overview regarding genetic and botanical characteristics as well as chemical profile and potential utilization of mate (Ilex paraguariensis St Hil.) plant. The major components present in parts of mate plant are reviewed and possible health problems arising from customarily intake of hot infusions are addressed. Likewise, important applications of mate as drinks, cosmetics, and pharmaceuticals are commented along with relevant properties in human health treatment. Finally, it is discussed the mate world wide market in perspective with special emphasis on the path from the industry environment to costumer consumption.
Keywords: Antioxidant activity; Breeding; Chemical profile; Genetic variability; Ilex paraguariensis